Combination of Osmotic Dehydration and Further Drying to Improve the Quality of Dried Carrots - Ranti - Ranti; Leopold Oscar Nelwan; Emmy - Darmawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The food industry needs carrots as a processed product for dry products using drying technology to maintain product quality. The aim of the research was to examine the effect of osmotic dehydration temperature with ternary solution on the quality of carrots. The treatments studied were osmotic media temperatures of 25°C and 50°C combined with oven drying and infrared until the water content reached ±10%. Parameters measured after osmotic dehydration were loss of water and increase in solids, quality parameters after further drying were water content and post-storage quality parameters were carotenoids and rehydration test. The dehydration treatment resulted in a reduction of water of 27.25%-44.24% and addition of solids of 15.37%- 18.31%. The initial water content of carrots before osmotic treatment was 90%, the water content after osmotic at 25°C was 65.72% and 50°C was 63.29%. Combination of osmotic with oven requires 22-24 hours of drying time while infrared requires 8- 10 hours of drying time. The best carotenoid value was osmotic dehydration at 25°C followed by an oven or infrared with a value of 32.95(mg/100g)–31.94(mg/100g). Whereas at 50°C the rehydration values were in the range 271.14%-301.42% Keywords: Carrots, Infrared drying, Osmotic dehydration, Osmotic solution, Oven drying